Pro XML Development with JavaTM Technology - Vohra, Ajay (Apress, 2012)
In this book, we have two main objectives. Our first objective is to discuss a selected subset of XML- related W3C Recommendations that have inspired corresponding Java APIs. And to that end, here is a quick synopsis of the XML-related W3C Recommendations and Java APIs that we’ll cover in this book